İDİOPATİK TROMBOSİTOPENİDE DOĞUM ŞEKLİ: 3 OLGU SUNUMU - ÖZTÜRK, Ebru; ATIŞ, Alev; ÖÇAL, Pelin; ÇEPNİ, İsmail and MADAZLI, Rıza (Cerrahpaşa Medical Journal, 2014)
Background.- The risk of the fetal or neonatal thrombocytopenia is very low in pregnant patients with ITP. It is accepted that no correlation exists between fetal or neonatal platelet counts and mother’s thrombocytopenia. Actually spontoneus vaginal delivery without antepartum or intrapartum fetal platelet determination was the most reasonable method of delivery for pregnant with ITP. If there is any obstetrical indication cesarean delivery is preferred. Observation.- We want to discuss 3 cases of ITP in pregnancy and the mode of deliveries with review of the literature .